Characterisation of batteries with E–P-curves: Quantifying the impact of operating conditions on battery performance. (July 2018) - Sarpal, Ishwar Singh; Bensmann, Astrid; Mähliß, Jochen; Hennefeld, Dominik; Hanke-Rauschenbach, Richard
Highlights: Battery performance characterisation with Ragone plots in absolute coordinates. Charge and Discharge characteristics for different initial state of charge. Influences of operating conditions on the energy-power relation are quantified. Most impact on battery performance is given for the max. discharge current. Abstract: Batteries find their application in various fields. The resulting requirements are characterised in terms of necessary power and energy. In this paper, we suggest to characterise batteries in the same coordinates by determining the energy for varying load power. The resulting E – P -curves can help to compare different cells in the relevant aspects and can be used to design battery storage systems. Therefore, we show the influence of different operating parameters on the charging as well as the discharging behaviour. These are the minimum voltage, the maximum discharge current, the maximum operating as well as the ambient temperature and the initial state of charge. If it is allowed to discharge the battery with a peak current for a short time, the influence can be quantified by the suggested method as well. The method is illustrated by taking different lithium-ion batteries as examples.